Analysis of Fuzzy and PID control in Pacemaker with cardiovascular model. Issue 1 (July 2021) - Manoj Srivatsn, S; Vamsi Venkata Sai Kumar, V; Sakthivel, G; Saravanakumar, D; Raghu Kiran, N
Abstract: Cardiac Pacemakers have been effectively implemented to balance the electrical conduction network of the heart; A pacemaker's primary function is to control an optimal heart rhythm, either because the elementary design of pacemaker of the heart is not quick enough, or because there is a barrier in the electrical conduction mechanism of the heart. Modern pacemakers are capable of external tuning and it enables optimal pacing modes for individual patients to be selected by a cardiologist, especially a cardiac electrophysiologist. In this study, linear and non-linear control logic for the regulation of the electrical response from the cardiac pacemaker has been studied with evaluation. The logic is constructed based on the mathematical model of the heart which has been converted from physiological model to electromechanical model. The pacemaker regulation, based on the control logic is evaluated on the grounds of the PQRST wave complex and the precision of the complex.